Enhancing Employee Engagement in Multinational Companies in Oman: An Exploration of Theoretical Concepts - Ghunaimi, Hisham Al; Kassim, Mohamad Shah Bin (Journal of Management World, 2024)
This research establishes a theoretical framework aimed at improving employee engagement within multinational corporations (MNCs) in Oman. By leveraging established theories and models, including Kahn's Engagement Theory and Herzberg's Motivation-Hygiene Theory, the framework fuses global best practices with local considerations to confront the specific challenges confronted by Oman's varied workforce and hierarchical organizational structures. A systematic literature review is utilized to gain a thorough understanding of the topic. Key findings indicate that leadership, cultural alignment, and employee well-being are critical to enhancing engagement. The study draws on a systematic review of Scopus-indexed journals and relevant industry reports from the region, providing valuable insights for HR professionals and policymakers in Oman's MNCs. This paper aims to close the gap between theory and practice by offering a culturally tailored approach to engagement. The framework stands out by integrating international theories with strategies specifically designed for the dynamics of Oman's workforce. Furthermore, the study highlights practical implications for HR professionals in sectors such as oil and gas, retail, and tourism, presenting actionable strategies that address the socio-economic and cultural challenges faced in Oman.